Saguenay Youth Study: A multi-generational approach to studying virtual trajectories of the brain and cardio-metabolic health. (February 2015) - Paus, T.; Pausova, Z.; Abrahamowicz, M.; Gaudet, D.; Leonard, G.; Pike, G.B.; Richer, L.
Highlights: Psychiatric conditions contribute the most to global health burden. Developmental cascades provide a framework for understanding causes and consequences. Multi-generational design enables studies of virtual health trajectories. Saguenay Youth Study is a multi-generational and multi-system cohort designed along these lines. Abstract: This paper provides an overview of the Saguenay Youth Study (SYS) and its parental arm. The overarching goal of this effort is to develop trans-generational models of developmental cascades contributing to the emergence of common chronic disorders, such as depression, addictions, dementia and cardio-metabolic diseases. Over the past 10 years, we have acquired detailed brain and cardio-metabolic phenotypes, and genome-wide genotypes, in 1029 adolescents recruited in a population with a known genetic founder effect. At present, we are extending this dataset to acquire comparable phenotypes and genotypes in the biological parents of these individuals. After providing conceptual background for this work (transactions across time, systems and organs), we describe briefly the tools employed in the adolescent arm of this cohort and highlight some of the initial accomplishments. We then outline in detail the phenotyping protocol used to acquire comparable data in the parents.